Perceptions of Men on Male Partners Involvement in Maternal and Child Health: An Analysis of Kuria East SubCounty, Migori County, Kenya - Maureen Kwamboka Nyabuto; Taji Isindu Shivachi; John Odero Sibuor; Wilson A.P. Otengah (Adventist University of Africa, 2023)
Background: Male partner involvement is critical to maternal and child health outcomes. In Kenya, male partners are entitled to a two-week paternal leave with full pay to encourage male partner support in antenatal and postpartum care services, breastfeeding, complementary feeding, and health education. However, the involvement of males in maternal and child health remains inadequate. This could be attributed to several factors. Consequently, this study investigated perceptions of men on male partner involvement in maternal and child health in Kuria East Sub-County, Migori County, Kenya Methods: This study used a mixed-method and descriptive cross-sectional survey research design. Questionnaires, Focus Group Discussions, and Key Informant Interviews were used to collect data. Two hundred and ninety-six respondents completed the questionnaire, six key informants took part in interviews, and fourteen participated in focus group discussions to investigate the perceptions of men on their involvement in maternal and child health. Results: Men's perceptions of male partners' involvement in maternal and child health vary. At the community level, there is a negative perception of male partners' involvement in maternal and child health. The community perceives maternal and childcare as a female's role. On the other hand, individual males generally have a positive view of male partners' involvement in maternal and child health. However, the study reveals that the age does not determine the perceptions of males on male partner involvement both at community and individual level whereas educational attainment and occupation have significant associations with the perceptions of males on male partner involvement in MCH. Conclusion: The study concludes that men's perception of male partners' involvement in maternal and child health varies. At the community level, there is a negative perception of male partners' involvement in maternal and child health. On the other hand, individual males generally have a positive view of male partners' involvement in maternal and child health.